Teacher Behavior Profile in Organization Citizenship Behavior: Profil Perilaku Guru dalam Organization Citizenship Behavior - Salim, Salim; Prajono, Rahmad; Nurhayati, Nurhayati; Abdin, Abdin; Saputra, Hendra Nelva (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this research is: (1) to reveal the portrait behavior of organizational citizenship behavior in primary school teachers in Kendari City, (2) to assess factors affecting the behavior of organizational citizenship behavior of teachers Primary school in the city of Kendari, (3) to analyze the difference in behavior of organizational citizenship behavior is reviewed from the gender of school status and gender in primary school teachers in Kendari City. This approach of research using a mixed-methods method combines qualitative and quantitative research. The place of implementation of this research is an elementary school in the region of Kendari, Southeast Sulawesi province. The results of this study show generally teachers of elementary school in the city of Kendari have organization citizenship behavior with good behavior, (2) Factors that influence the behavior of organizational citizenship behavior of Teachers Elementary School in Kendari City is a school climate that encompasses work culture, school leadership management, and school objectives, (3) There is no difference in organizational citizenship behavior Behaviour for elementary school teachers in Kendari City is reviewed from Gender, school status, and school type.